The Donkey’s Song: Aldo Palazzeschi’s Canzonetta "Let Me Have My Fun" (1910) in the History and Mythology of Russian (Anti-)Futurism - Ilya Vinitsky (Studi Slavistici)
Parodies, caricatures, mockery, and scathing remarks by critics often serve as provocative invitations to explore the reception and interpretation of literary experiments within their respective cultural contexts. This kind of literary interpretation “by means of contradiction” might be termed boo-criticism. This article examines a vivid example of such criticism, introducing a characteristic mythopoetic figure that emerged from the heated literary polemics of the 1910s. Taking as its point of departure Vasilij Rozanov’s panic-stricken critique of contemporary literature as a ‘kingdom of donkeys’ – a vision that arguably echoes Aldo Palazzeschi’s transrational stanza in Let Me Have My Fun! – the article traces the motif’s origins in Nietzsche and its elaboration in the Russian avant-garde (Kručënych, Gončarova, Majakovskij, Zdanevič).